2010
DOI: 10.2993/0278-0771-30.1.153
|View full text |Cite
|
Sign up to set email alerts
|

Uses and Taboos of Turtles and Tortoises Along Rio Negro, Amazon Basin

Abstract: Chelonians (turtles and tortoises) of the Amazon Basin have constituted a source of food for native populations since pre-Columbian times and have continued to be an important product for subsistence and cash income. Little is known about current levels of exploitation and pressure on natural stocks, despite observations of declining populations of the larger and most valued species. This study investigates how people living in the Negro River area use Amazonian chelonians, including issues of consumption, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 22 publications
1
38
0
8
Order By: Relevance
“…Our purpose is to describe the techniques for capturing turtles and the ways in which they were utilized by two ethnic groups. The turtle fauna of this trans-Andean locality is entirely cryptodiran and taxonomically distinct from the Amazonian pleurodires and tortoises that have frequently been described in other studies of South American turtle use (e.g., Johns, 1987;Fachín-Terán et al, 2004;Pezzuti et al, 2010;Castro Casal et al, 2013). Also, the primary inhabitants of northwestern Ecuador are Afroecuadorians, a population with little published concerning their interactions with wildlife (West, 1957;Whitten, 1974).…”
Section: Introductionsupporting
confidence: 50%
“…Our purpose is to describe the techniques for capturing turtles and the ways in which they were utilized by two ethnic groups. The turtle fauna of this trans-Andean locality is entirely cryptodiran and taxonomically distinct from the Amazonian pleurodires and tortoises that have frequently been described in other studies of South American turtle use (e.g., Johns, 1987;Fachín-Terán et al, 2004;Pezzuti et al, 2010;Castro Casal et al, 2013). Also, the primary inhabitants of northwestern Ecuador are Afroecuadorians, a population with little published concerning their interactions with wildlife (West, 1957;Whitten, 1974).…”
Section: Introductionsupporting
confidence: 50%
“…In Brazil, Freiberg (1954), Alho (1985), Rocha andMolina (1990), Vogt (2008), and Carvalho et al (2010) reported that this turtle is sold on beaches, in markets, and in restaurants, despite current legislation restricting that activity, and Nóbrega Alves et al (2008) reported on its supposed medicinal value. Pezzuti et al (2010) found that it is rarely found or consumed along the Rio Negro in Brazil; however, no published records are known from that specific drainage.…”
Section: 8mentioning
confidence: 98%
“…"Taboos" refer to informal http://www.ecologyandsociety.org/vol20/iss4/art21/ institutions imposed by social custom that might influence food consumption through dietary prohibition or avoidance of certain resources (e.g., freshwater dolphins, tapirs), periods of time (e.g., certain seasons), or by societal subgroups (e.g., pregnant women, ill people; Ross et al 1978). In the Amazon, some animals are referred to as reimosos, or of being capable of causing inflammation or illness in certain people, and are thus tabooed (Pezzuti et al 2010). Higher values indicate agreement with the opinion that taboos are important and should be followed.…”
Section: Explanatory Variables: Cultural and Economic Correlatesmentioning
confidence: 99%